Ex vivo engineered immune organoids for controlled germinal center reactions. (September 2015) - Purwada, Alberto; Jaiswal, Manish K.; Ahn, Haelee; Nojima, Takuya; Kitamura, Daisuke; Gaharwar, Akhilesh K.; Cerchietti, Leandro; Singh, Ankur
Abstract: Ex vivo engineered three-dimensional organotypic cultures have enabled the real-time study and control of biological functioning of mammalian tissues. Organs of broad interest where its architectural, cellular, and molecular complexity has prevented progress in ex vivo engineering are the secondary immune organs. Ex vivo immune organs can enable mechanistic understanding of the immune system and more importantly, accelerate the translation of immunotherapies as well as a deeper understanding of the mechanisms that lead to their malignant transformation into a variety of B and T cell malignancies. However, till date, no modular ex vivo immune organ has been developed with an ability to control the rate of immune reaction through tunable design parameter. Here we describe a B cell follicle organoid made of nanocomposite biomaterials, which recapitulates the anatomical microenvironment of a lymphoid tissue that provides the basis to induce an accelerated germinal center (GC) reaction by continuously providing extracellular matrix (ECM) and cell–cell signals to naïve B cells. Compared to existing co-cultures, immune organoids provide a control over primary B cell proliferation with ∼100-fold higher and rapid differentiation to the GC phenotype with robust antibody class switching.